Analysis of Event Management for the Singing Competition at Polbeng Business Expo Chapter II (Case Study of Project Manager) - Sinta Amanda; Armita Novriana Rambe (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the role of the Project Manager in organizing the Elementary and Junior High School Spelling Bee Competition at Polbeng Business Expo Chapter II, particularly in managing event implementation, addressing challenges, and applying appropriate solutions to ensure the successful execution of the event. This study employed a qualitative descriptive approach using interviews and observations as data collection techniques. The collected data were analyzed through thematic analysis to identify the Project Manager’s roles, challenges encountered during the event, and strategies implemented to overcome them. The findings indicate that the Project Manager played a significant role in project planning, progress monitoring, effective communication, and media strategy development. Several challenges were identified during the event, including participant delays, team coordination issues, and technical disruptions that affected the implementation process. To address these challenges, the Project Manager implemented contingency plans, established clear communication and structured task distribution, and conducted routine evaluations to ensure that the event remained aligned with the predetermined objectives. The findings highlight the importance of effective project management practices, adaptive decision-making, and continuous coordination in supporting the successful implementation of educational events within a MICE-based environment while providing practical recommendations for organizing similar educational events effectively in the future.